Psychology and aggregation in International Relations. (September 2020) - Gildea, Ross James
Theories of decision-making grounded in political psychology have experienced a dramatic rise in the study of International Relations. There is widespread recognition of the benefits of incorporating insights from the behavioural sciences into analyses of political behaviour. However, some scholars have argued that the theoretical and empirical scope of these perspectives remains hampered by an unresolved issue: aggregation. While the fundamental unit of interest in psychology is the individual, most International Relations models concern patterns of collective decision-making in aggregate units such as states, bureaucracies, armed groups, transnational networks and institutions. This article contributes to the aggregation debate by providing a more optimistic portrait of its implications for interdisciplinary work. I argue that aggregation may be an overstated problem in International Relations and that a disciplinary preoccupation with it may hinder rather than pave the way for interdisciplinary theorizing.